DESORPSI ION EMAS(III) DALAM SISTEM MULTILOGAM AU/NI/AG DENGAN MENGGUNAKAN VARIASI TIOUREA-HCL - Manuhutu, Julita; Nuryono, Nuryono; Santosa, Sri Juari (Molluca Journal of Chemistry Education (MJoCE), 2018)
Desorption of gold(III) in multi-metal system Au/Ni/Ag on amino silica hybrid (ASH) column have been studied. ASH was synthesized by sol gel process with sodium silicate (Na2SiO3) from rice husk ash (RHA) as precursor. ASH was synthesized by adding 3M of hydrochloride acid solution to the mixture of (3-aminopropyl)-trimethoxysilane and Na2SiO3 solution untill pH 7 (neutral). ASH was characterized by infrared spectroscopy (IR) and X-ray diffraction (XRD). Adsorption of multi-metal (Au/Ni/Ag) was carried out with a column technique. The adsorbed metal ions [Au(III), Ni(II), and Ag(I)] were quantitively using atomic absorption spectroscopy (AAS). Desorption of Au(III), Ni(II), and Ag(I) at ASH was conducted by using thioruea in hydrochloride solution with variation of concentration. Total desorption of metal ions was calculated based on AAS analysis. For desorption of multi-metal(Au / Ni / Ag), Au (III) was eluted using 1M HCL is 16,60%; using 0,5 M thiourea in 1M HCl is 57,45%, and with 1M thiourea in 1M HCl is 59,12%.